USM PURSUING FURTHER COLLABORATIONS WITH AN ALLIANCE OF 4 UNIVERSITIES (A-4U) FROM SPAIN - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 1 March 2017 Universiti Sains Malaysia (USM) ViceChancellor, Professor Datuk Dr. Asma Ismail today welcomed a courtesy visit to USM from the delegates of Institutional of A4U (Alliance of 4 Spanish Universities) at the Chancellory Conference Room, Chancellory Building, here.